Analisa Pengambilan Keputusan Pemilihan Venodr Seragam Dengen Merode Analytical Hierarchy Proces (AHP) ( Studi Kasus General Affairs PT Penjallindo Nusantara) - Imas Widowati; Daisy Ade Riany Diem; Wanwan Jamaludin; Eka Sukmawati Sukma (Jurnal Teknologika, 2023)
Decision makers need analytical tools that allow them to solve problems. Decisions to be taken are complex with major risks such as policy formulation, decision makers often need tools in scientific, logical, and structured forms. To determine the priority stages of criteria in order to obtain the most optimal results in returning uniform vendor selection decisions at PT Penjalindo Nusantara (Metaform) using the AHP (Analytical Hierarchy Process) method. In essence, AHP is a comprehensive decision-making model by taking into account qualitative and quantitative matters. There are three main principles in problem solving in AHP, namely: Decomposition, Comparative Judgment, and Logical Concistency. Bycomparing in pairs to determine the priority weight on each criterion and alternative. One of the paired comparisons is carried out in pairwise comparisons between criteria. Vendor selection criteria include quality, price, flexibility, delivery and service criteria. . Compiling alternatives that have been determined in the form of matirx in order to obtain the assessment weight of each variable, a table of pair comparison rating scales is made. Based on the results of the AHP calculation, each weight for each venodr is obtained PT Intan of 0.62860 and the weight value of the Super Decision is 0.638683. PT Parahita as a vendor with a weight value of 0.20475 and a weight value in Super Decision of 0.203985. PT Marcapada with a weight value of 0.16665 and a weight value in Super Decision of 0.159189. So the main uniform supplier is PT Intan with the largest weight.